Green synthesis of nanohydroxyapatite trough Elaeagnus angustifolia L. extract and evaluating its anti-tumor properties in MCF7 breast cancer cell line - Asghar Zarban; Ehsaneh Azaryan; Maryam Moradi Binabaj; Samira Karbasi; Mohsen Naseri (BMC Complementary Medicine and Therapies, 2023)
Abstract Background One of the most common types of cancer in women is breast cancer. There are numerous natural plant-based products, which exert anti-tumoral effects including Elaeagnus Angustifolia (EA). It modulates cell-cycle process, heat-shock proteins expression, anti-proliferative properties, apoptosis induction, blocking of angiogenesis, and cell invasion inhibition. The current study aimed to synthesize and evaluate the anticancer effects of hydroalcoholic EA extract (HEAE), Nanohydroxyapatite (nHAp) and nHAp synthesized trough EA (nHA-EA) in MCF-7 breast cancer cell line. Methods In the present study, HEAE preparation and green synthesis of nHA-EA was done and phase composition, functional groups, and crystallin phase of nHA-EA and nHAp were determined using Fourier-transform infrared (FTIR) and X-ray diffraction (XRD). The characteristics of synthesized nanoparticles including structural and morphological parameters were investigated using scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) techniques. Then, by using MTT-assay (Dimethylthiazoldiphenyltetrazolium), the in vitro cytotoxic and half maximal inhibitory concentration (IC50) of EA extract, nHAp, and nHA-EA in the MCF-7 breast cancer cell line was evaluated. Next, we assessed the expression of apoptosis-related genes Bax, Bcl2 and p53 using quantitative reverse-transcriptase polymerase-chain-reaction (qRT-PCR) and migration of MCF-7 cells by scratch assay. Results The FTIR results demonstrated formation of nHAp and its interaction with HEAE during synthesis process. The XRD results of the synthesized nanoparticles showed similar XRD pattern of nHA-EA and nHAp and purity of synthesized nanomaterials. The average IC50 of HEAE, nHAp, and nHA-EA extract after treatment of cancer cells for 24 h was 400 µg/mL, 200 µg/mL, and 100 µg/mL, respectively. Our results revealed that nHA-EA significantly reduced the migration and invasion of the MCF-7 cells, in comparison to the nHAp and EA extract. Moreover, level of Bax/Bcl2 and p53 was significantly higher in the nHA-EA extract group in comparison to the EA extract and nHAp group. Conclusion Taken together, our results demonstrated that bioactive constituents of EA medicinal plant in form of nHA-EA particles, can effectively exerts potential anticancer and chemo preventive effect against breast cancer growth and can be proposed as a promising beneficial candidate for BC therapy. However, further investigations are required to discover what bioactive compounds are responsible for the chemo preventive effect of this extract.